An Efficient Chaos-Based Feedback Stream Cipher (ECBFSC) for Image Encryption and Decryption - Ahmed, H.E.H.; Kalash, H.M.; Allah, O.S.F. (Informatica)
An Efficient Chaos-Based Feedback Stream Cipher (ECBFSC) for Image Encryption and Decryption